Balancing stakeholder priorities for sustainable land management - Verbist, Joren; Akramkhanov, Akmal; Lautze, Jonathan (2024)
The present blog informs about the development of a Support System (DSS) tool to support stakeholders in decision-making on implementing Sustainable Land Management practices. The DSS tool was constructed on the basis of a literature review and survey data. Literatures used in the development of the tool derived from the World Overview of Conservation Approaches and Technologies (WOCAT) database. The survey data has been primarily collected among farmers and experts.